An Empirical Study on Rural Marketing Opportunities and threads in India - V. Obulesu, P. Prasanna Kumar, G. Naga Ramesh Babu (Mathematical Statistician and Engineering Applications, 2023)
Rural Marketing is gaining in its importance as a force of economic change that must take place if many rural communities are to survive.The Urban markets are maturing and high level of competition ruining the profit margins. The urban consumers being too much advanced expect new products in small intervals thereby reducing life span of the products,Rural Marketing is now a days a play a role major opportunity for the people who migrate from rural areas people or semi urban people areas to Urban areas peoples. On the other hand rural income graph is on a rise, which has given huge scope to the corporates to tap this market where 70% of India resides. The study aims to provide information on how the corporates carry out the marketing process and the reasons for the paradigm shift from Urban to Rural markets. These are the market for consumer goods that comprise of both durable and non-durable goods and the market for agricultural inputs. Rural incomes are growing due to green revolution, rise in agri-produce prices, Skilled India programs, financial inclusion, etc. preferences of rural people are also getting changed.